Formulation And Evaluation of Herbal Mouthwash - Phadtare, Dipti G.; Wagh, Rohini P.; Hon, Abhijit S.; Kendre, Vaishnavi J.; Gangurde, Aditya K.; Mohan, Amol R.; Desai, Sakshi R. (Journal of Neonatal Surgery, 2025)
Herbal mouthwash presents a compelling natural alternative to conventional chemical-based oral care products. Formulated with time-honored botanicals such as honey, amla (Emblica officinalis), nagarvel (Piper betle), and guava (Psidium guajava) leaves, this plant-based solution leverages the powerful antimicrobial, anti-inflammatory, and antioxidant benefits of Ayurvedic medicine. These ingredients work in harmony to minimize plaque buildup, fight harmful oral bacteria, alleviate gum irritation, and promote lasting breath freshness all without the use of alcohol or synthetic additives. Supported by scientific research validating its effectiveness in reducing microbial load and improving oral hygiene, herbal mouthwash stands out as a safe, eco-conscious, and holistic choice for maintaining dental health naturally. Its growing popularity reflects a broader shift toward sustainable and health-conscious personal care